2021
DOI: 10.1037/sah0000246
|View full text |Cite
|
Sign up to set email alerts
|

Self-stigma, resilience, perceived quality of social relationships, and psychological distress among Filipina domestic helpers in Hong Kong: A mediation model.

Abstract: Filipina domestic helpers (FDH) make up nearly 3% of the Hong Kong population. Research suggests that FDH are at risk for self-stigmatization and poor mental health. However, little is known about how FDH’s self-perceptions and individual characteristics are associated with their perceived quality of social relationships and mental health. This study examined how self-stigma and resilience might be associated with psychological distress among FDH in Hong Kong and how perceived quality of social relationships (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Fourth, our sample was quite highly educated, with more than half of the sample reported to have college education. However, local studies among Southeast Asian domestic helpers reported comparable education levels with our sample (over 90% received secondary and tertiary education) [25,54]. Generalizations of our findings to FDHs with different demographic characteristics must be made with caution.…”
Section: Limitationssupporting
confidence: 51%
See 3 more Smart Citations
“…Fourth, our sample was quite highly educated, with more than half of the sample reported to have college education. However, local studies among Southeast Asian domestic helpers reported comparable education levels with our sample (over 90% received secondary and tertiary education) [25,54]. Generalizations of our findings to FDHs with different demographic characteristics must be made with caution.…”
Section: Limitationssupporting
confidence: 51%
“…It has been found that FDHs' opportunities to seek emotional and material support from their peers might have been reduced due to the COVID-19 pandemic and social distancing measures [20]; the role of social support is, therefore, important. Previously, the protective role of social support in psychological well-being was found among Filipina domestic helpers in Hong Kong [25]. We expected that social support would be associated with lower anxiety symptoms among FDHs coping with the COVID-19 pandemic.…”
Section: Social Support Covid-19 Information Literacy and Anxiety Symptomsmentioning
confidence: 86%
See 2 more Smart Citations
“…Hierarchical regressions were conducted to examine the associations between the independent variables and adversarial growth. The sequence of entering independent variables followed the suggestions from prior studies applying the Stress and Coping model in the contexts of chronic illnesses and other traumatic events (Yeung et al, 2016, 2020). In the first step, COVID-19 distress, work-related stress, and background variables showing significant associations with adversarial growth in bivariate correlations were entered.…”
Section: Methodsmentioning
confidence: 99%